Cloning of TaeRF1 gene from Caucasian clover and its functional analysis responding to low-temperature stress - Zhang, Xiaomeng; Jiang, Jingwen; Ma, Zewang; Yang, Yupeng; Meng, Lingdong; Xie, Fuchun; Cui, Guowen; Yin, Xiujie (Frontiers in Plant Science, 2022)
Low temperature (LT) is an important threat to the normal growth of plants. In this study, based on the full-length transcriptome sequencing results, the cold resistance genes were cloned from Caucasian clover with strong cold resistance. We cloned the CDS of TaeRF1, which is 1311 bp in length and encodes 436 amino acids. The molecular weight of the protein is 48.97 kDa, which had no transmembrane structure, and its isoelectric point (pI) was 5.42. We predicted the structure of TaeRF1 and found 29 phosphorylation sites. Subcellular localization showed that TaeRF1 was localized and expressed in cell membrane and chloroplasts. The TaeRF1 gene was induced by stress due to cold, salt, alkali and drought and its expression level was higher in roots and it was more sensitive to LT. Analysis of transgenic A. thaliana plants before and after LT treatment showed that the TaeRF1 gene enhanced the removal of excess H2O2, and increased the activity of antioxidant enzymes, thus improving the plant's ability to resist stress. Additionally, the OE lines showed increased cold tolerance by upregulating the transcription level of cold-responsive genes (CBF1, CBF2, COR15B, COR47, ICE1, and RD29A). This study demonstrates that TaeRF1 is actively involved in the responses of plants to LT stress. We also provide a theoretical basis for breeding and a potential mechanism underlying the responses of Caucasian clover to abiotic stress.